2013
DOI: 10.1111/aas.12170
|View full text |Cite
|
Sign up to set email alerts
|

Skin temperature measured by infrared thermography after ultrasound‐guided blockade of the sciatic nerve

Abstract: After sciatic nerve block, temperatures of the foot increased significantly. There was a good correlation between pinprick testing and infrared temperature measurement. This makes infrared skin temperature measuring a good test in determining block success when sensory testing is impossible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…It has been speculated that direct chemical or pharmacological stimulation of afferent thermal fibres by the local anaesthetic might cause this phenomenon . The increase of skin temperature has been reconfirmed by several authors . It is also detectable in geriatric patients and infants .…”
Section: Skin Temperature As An Indicator Of Regional Anaesthesia Sucmentioning
confidence: 71%
See 1 more Smart Citation
“…It has been speculated that direct chemical or pharmacological stimulation of afferent thermal fibres by the local anaesthetic might cause this phenomenon . The increase of skin temperature has been reconfirmed by several authors . It is also detectable in geriatric patients and infants .…”
Section: Skin Temperature As An Indicator Of Regional Anaesthesia Sucmentioning
confidence: 71%
“…More proximally, no temperature changes were detected. Since skin temperature increased before pinprick sensation was reduced the authors concluded that skin temperature measurement represents a good test for determining block success when sensory testing is impossible …”
Section: Skin Temperature As An Indicator Of Regional Anaesthesia Sucmentioning
confidence: 99%
“…14 In addition, the sympathetic portion of the three investigated nerves is not described (different to, e.g. the sciatic nerve, where a large portion of sympathetic fibres can be assumed 15 ) and may differ between the three nerves.…”
Section: Sensory Testingmentioning
confidence: 99%
“… and van Haren et al. . Similarly, higher sensitivity and specificity were found for perfusion indices .…”
Section: Testing Of Onset and Assessing Readiness For Surgerymentioning
confidence: 75%
“…Methods based on change in skin temperature resulting from sympathetic blockade have been explored as an indicator for block success. Skin temperature has been measured by infrared thermography , with a thermometer or by simply feeling the patient's skin . In addition, a brief case report described how a patient's temperature‐sensitive nail varnish changed colour after onset of a peripheral nerve block of the arm in question!…”
Section: Testing Of Onset and Assessing Readiness For Surgerymentioning
confidence: 99%